The Effects of a Pedagogical Agent’s Smiling Expression on the Learner’s Emotions and Motivation in a Virtual Learning Environment - Liew, Tze; Azan Mat Zin, Nor; Sahari, Noraidah; Tan, Su-Mae (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2016)
The present study aimed to test the hypothesis that a smiling expression on the face of a talking pedagogical agent could positively affect a learner’s emotions, motivation, and learning outcomes in a virtual learning environment. Contrary to the hypothesis, results from Experiment 1 demonstrated that the pedagogical agent’s smile induced negative emotional and motivational responses in learners. Experiment 2 showed that the social meaning of a pedagogical agent’s smile might be perceived by learners as polite or fake. In addition, qualitative data provided insights into factors that may cause negative perceptions of a pedagogical agent’s smile, which in turn lead to negative affective (emotional and motivational) states in learners. Theoretical and design implications for pedagogical agents in virtual learning environment are discussed in the concluding section of the paper.